Collaboration and informal hierarchy in innovation teams: Product introductions in entrepreneurial ventures - Lahiri, Amrita; Pahnke, Emily C.; Howard, Michael D.; Boeker, Warren (Strategic Entrepreneurship Journal, 2019)
Abstract Research Summary Although stars may be particularly innovative, building teams to collaborate with them can be difficult. Coordinating efforts between stars and non‐stars may be especially complex in new venture, which rely on informal hierarchy to manage organizational tasks. We investigate how a venture's success at introducing new products may be influenced by the extent to which company founders and star performers are involved in co‐developing new technologies. By analyzing innovation teams within a sector of the medical device industry from 1986 to 2007, we find that combining both star inventors and founder‐inventors on a venture's innovation team may limit product introductions. Our results highlight the importance of organizational design in managing coordination and resource allocation in a venture setting and suggest important boundary conditions when stars may impede, rather than benefit, innovation. Managerial Summary Designing an innovation team can be challenging for new ventures. While the presence of a technologically proficient founder or highly accomplished inventor can significantly bolster a new venture's innovation efforts, our results indicate that these roles must be carefully managed to prevent conflicts between them. Our findings suggest that founders who hire star inventors should establish a clear hierarchy of decision‐making within innovation teams, while also offering greater autonomy to the star inventor in matters concerning innovation leadership and product development. We also suggest that it may be advantageous for founders to hire star inventors with prior experience working in new ventures as opposed to older, established organizations. Overall, our study indicates that new ventures need to exercise caution in hiring and managing star employees.